Visually Challenged Students’ Proficiency in the Use of Abacus - Singh, Lavalesh Pratap; Rai, Adya Shakti (JOURNAL OF INDIAN EDUCATION, 2014)
Abacus is a device, useful for visually challenged students as it presents mathematical operations in tactile form. Training in the use of abacus is a must at elementary level. Proficiency in the use of abacus is essential to visually challenged students, not only for learning higher level mathematics but also for their independent living. This study has been carried out with an objective to study elementary level visually challenged students’ proficiency in the use of abacus. Findings of the study show that their level of proficiency is very low. Although students in the given sample are little aware of the history of the abacus very few of them know about basic operations like addition and subtraction. They were totally unaware of the functions like multiplication, division, decimal and fraction. It also shows that learning to use an abacus is a big challenge for them.